Molecular dynamics study of the scratching property of the tetrahedral amorphous carbon coating on the piston ring - Zhao, Xiaowei; Lü, Yanjun; Chen, Ruibo; Yang, Xinliang; Zhang, Yongfang; Kang, Jianxiong (Molecular physics, 2025)
In order to reduce friction and wear of the piston ring-cylinder liner system of the internal combustion engine, the tetrahedral amorphous carbon (ta-C) coating on the piston ring is considered. The scratching properties of the ta-C coating and diamond ball are studied by molecular dynamics simulation. The atomic configuration, surface morphology, RMS roughness, friction force, coefficient of friction, wear rate, and normal stress of the ta-C coating are analysed under different scratching depths, substrate temperatures, and scratching velocities. The interatomic interactions are described using the second nearest-neighbour modified embedded-atom method potential, as well as Tersoff potential and Lennard-Jones potential. The simulation results show that the ta-C coating exhibits excellent scratching properties. The scratching depth has a significant effect on the scratching property of the ta-C coating, while the substrate temperature and scratching velocity have a relatively small effect.